Hashimoto’s thyroiditis: from pathogenesis to clinical management - Wang, Linghui; Zhu, Xi; Xu, Shuting; Zhou, Bin; Wu, Yong; Li, Zhouting; Zhao, Yanjie; Li, Shuhui; Cheng, Feng; Zhu, Lei (Frontiers in Endocrinology, 2026)
Hashimoto’s thyroiditis (HT) is a chronic autoimmune thyroiditis characterized by thyroid-specific autoantibodies (TPOAb, TGAb) positivity and lymphocytic infiltration, and is a major cause of hypothyroidism in iodine-sufficient regions. Epidemiological data show a significant increase in the prevalence of HT, which is about four times more common in adult women than in men. The pathogenesis of HT involves a complex interaction of genetic susceptibility, environmental factors, and immune regulation. Its clinical diagnosis is mainly based on serological tests (TPOAb/TGAb) and thyroid ultrasound features. The current treatment of Hashimoto’s is based on levothyroxine (T4) replacement. This article presents a narrative review of the pathogenesis, status, and challenges of treatment of HT to provide a theoretical basis for optimizing clinical practice and basic research.